Fractures in the elderly - Koval, Kenneth J; Zuckerman, Joseph D (Lippincott - Raven Publishers, 1998)
This volume offers practical, expert guidance on the management of fractures in elderly patients. The first part of the book addresses general issues such as epidemiology of fractures in the elderly, metabolic bone disease, principles and aims of fracture management, outcome assessment, preoperative medical evaluation, anesthesia, postoperative complications, rehabilitation in the elderly, and management of multiply injured patients. The second part covers fractures in specific anatomic regions. The book concludes with discussions on the treatment of pathological fractures, non-union and malunion, and osteomyelitis.
Keywords: fraktury kostí; Aged; chirurgie; senioři; Fractures, Bone